2016
DOI: 10.1088/0953-8984/29/1/014004
|View full text |Cite
|
Sign up to set email alerts
|

Nematic liquid crystals on sinusoidal channels: the zigzag instability

Abstract: Abstract.Substrates which are chemically or topographically patterned induce a variety of liquid crystal textures. The response of the liquid crystal to competing surface orientations, typical of patterned substrates, is determined by the anisotropy of the elastic constants and the interplay of the relevant lengths scales, such as the correlation length and the surface geometrical parameters. Transitions between different textures, usually with different symmetries, may occur under a wide range of conditions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…More recently, zigzag shaped disclinations have been observed also in NLCs confined to microwrinkle grooves 12,37 and were theoretically studied within a Landau-de Gennes model. 38 In these studies 12,[34][35][36][37][38] it was argued that the elastic anisotropy of NLCs is at the origin of the zigzag disclinations: because twist deformations of the director field cost significantly less elastic energy than splay or bend deformations, disclination lines form under the boundary conditions of the above mentioned studies in the twist configuration and release some twist energy by inclining and forming the zigzag pattern.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…More recently, zigzag shaped disclinations have been observed also in NLCs confined to microwrinkle grooves 12,37 and were theoretically studied within a Landau-de Gennes model. 38 In these studies 12,[34][35][36][37][38] it was argued that the elastic anisotropy of NLCs is at the origin of the zigzag disclinations: because twist deformations of the director field cost significantly less elastic energy than splay or bend deformations, disclination lines form under the boundary conditions of the above mentioned studies in the twist configuration and release some twist energy by inclining and forming the zigzag pattern.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…If we assume that the elastic distortions are on the xy plane, the conclusion is that the anchoring transition, which corresponds to moderate values of λ, may be shifted by this contribution, although qualitatively it will be very similar. However, if the twist elastic constant is smaller than K, there is experimental [11] and numerical [48] evidence of a twist instability which breaks the azimuthal symmetry: the disclination line is no longer parallel to the z axis, but exhibits a zig-zag structure which decreases the splay and bending dist ortions. This cannot happen in the sawtooth and crenellated substrates, since the disclination-like singularities are located at the surface cusps.…”
Section: The Sinusoidal Substratementioning
confidence: 99%
“…In addition, the interplay between interfacial configurations (as well as the substrate relief) and the orientational order in the nematic phase generates a plethora of distinct interfacial states, leading to rather complex interfacial phase diagrams [36]. In this context, systematic studies of the wetting for sawtooth [36,37], sinusoidal [38,39] and crenellated substrates [40,41] have been reported within the Landau-de Gennes theory. These studies revealed complex phase diagrams which differ considerably from their simple fluids counterparts.…”
Section: Introductionmentioning
confidence: 99%